Pelatihan Keterampilan Computational Thinking Bagi Guru SD di Nagari Kapau Kabupaten Agam Sumatera Barat - Erwinsyah Satria; Hendrizal Hendrizal; Daswarman Daswarman; Ira Rahmayuni Jusar (Universitas Persada Indonesia YAI, 2023)
Elementary school teachers need to master the 21st century skills needed in teaching, namelycritical thinking, creative, collaboration and communication skills. For this effort the author needsto provide knowledge on how teachers can recognize and apply 21st century skills to be used intheir teaching in the classroom. One of them is by providing training on computer thinking skills(computational thinking) to elementary school teachers in the Kapau area, Tilatang KamangDistrict, Agam Regency by making programming using the Scrath application to be used to createlearning media. The training carried out received a fairly good response from the teachers whoattended and they stated that the application used was very suitable for teaching and used byelementary school children and very interested in being able to later apply it to their students inclassroom learning.